MARKETING IN EDUCATION: TRENDS IN PRACTICE AND RESEARCH - ZAHAROVA Inna (Высшее образование в России)
The purpose of the article is to analyze which marketing tools are most important for higher education and can be used for effective administrative, financial and economic activities of universities. The article presented the trends in the development of education marketing in Russia, describes the marketing complex of the University, methods for assessing its competitiveness and demand for educational programs. The necessity of applying the principles of non-profit marketing in higher education is substantiated. The study used analytical and empirical methods, an interdisciplinary review of the literature on an investigated problem. Main conclusion: the effectiveness of marketing management for higher education.